ASSOCIATIVE AND DISSOCIATIVE RESPONSES IN THE LEARNING ENVIRONMENT - Fatmala, Nila (Tarbiyah and Teaching Training Faculty, 2016)
This research is intended to investigate the social interaction strategies experienced by Thailand students in Maulana Malik Ibrahim State Islamic University, Malang. As the foreigner students, they may experience associative and dissociative responses to construct self adjustment with their educational circumstance. Associative responses refer to positive feelings, kinship, and cooperation among students when they are interacting with the local students. In contrast, dissociative responses show the negative feelings, disintegration or even conflict. Those different reactions can generally occur when the foreigner students have been introduced new norms or cultures by the local students that are not similar to theirs. After gathering and analyzing the data from the research subject, the research accentuates that the awareness on the self negative and positive responses can perpetuate the social tolerance between the Thailand students and local students that can support their academic achievement.